(3QSGdI GdWjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3QSGdI GdWjQ ddTjN GdQFjS CHj Ydi Hf SjfG gd dCMO ef CNhGfi ai Cf jgH di ef SeYg bOQ eG Cdbi Edjg WQakG ef CTLGfi s
(3BNQgG (B:s
(3hdGNJdGd MGdc eNJdI eG CcKQ eG jbhdhf hbdeG hTQ GdebGd eG VGY hSjYde GdPjf XdehG Ci efbdH jfbdHhf JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdYGTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs